DISTRIBUTION OF STRUCTURAL IMPURITIES IN DIAMONDS OF DIFFERENT ORIGIN - Blinova G.K. (My University, 1989)
We studied diamond crystals from kimberlites, including colorless octahedra, rhombododecahedra, less often cubes, and forms transitional between them, and from metamorphic rocks, including yellow and yellow-green cubes, cuboids, a lesser number of octahedra, and combined forms of the cube-rhombododecahedron-octahedron series. The specimens measured at least 0.3 mm. The standard technique of IR spectroscopy was used. Both kimberlite and metamorphogenic diamonds show a correlation between habit and the degree of association of impurity nitrogen. The degree of association of nitrogen has been found to be a function of temperature and rate of growth of the crystal (or duration of postcrystallization annealing). Thus, the ratio of the concentrations of A1, B1 and B2 nitrogen centers in kimberlites of N, A, B1 and B2 centers in metamorphogenic diamonds may be regarded as an index of the temperature at which they were generated.